2008
DOI: 10.5005/jcdp-9-1-98
|View full text |Cite
|
Sign up to set email alerts
|

An Accessory Mental Foramen: A Case Report

Abstract: Aim The aim of this article is to present a case of an accessory mental foramen (AMF). Background The mental foramen is an important anatomical structure of particular importance in local anesthesia and surgical procedures in terms of achieving effective mandibular nerve blocks and avoiding injuries to the neurovascular bundles. Although rare, multiple mental foramina have been described in humans. In these cases one foramen is termed the mental foramen and the others are referred to as an AMF. Report A 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 6 publications
1
26
0
2
Order By: Relevance
“…Terms such as double mental foramina (Igarashi et al, 2004;Arx et al, 2014), additional mental foramina (Santos et al, 2013), multiple mental foramina, accessory mandibular foramina (Patil et al, 2013) and accessory buccal foramina ) have been used to describe AMFs. Many authors have defined 'AMF' as any foramen in addition to the MF in the lateral body of mandible (Mraiwa et al, 2003;Prabodha and Nanayakkara, 2006;Ca girankaya and Kansu, 2008;Singh and Srivastav, 2011;Thakur et al, 2011;Gupta and Soni, 2012;Jha and Kumar, 2012;Ahmed et al, 2014;Paraskevas et al, 2014;Rai et al, 2014). Some have described an AMF as a small foramen in the area surrounding the MF (Riesenfeld, 1956;Sutton, 1974).…”
Section: Definition Of An Amfmentioning
confidence: 99%
See 1 more Smart Citation
“…Terms such as double mental foramina (Igarashi et al, 2004;Arx et al, 2014), additional mental foramina (Santos et al, 2013), multiple mental foramina, accessory mandibular foramina (Patil et al, 2013) and accessory buccal foramina ) have been used to describe AMFs. Many authors have defined 'AMF' as any foramen in addition to the MF in the lateral body of mandible (Mraiwa et al, 2003;Prabodha and Nanayakkara, 2006;Ca girankaya and Kansu, 2008;Singh and Srivastav, 2011;Thakur et al, 2011;Gupta and Soni, 2012;Jha and Kumar, 2012;Ahmed et al, 2014;Paraskevas et al, 2014;Rai et al, 2014). Some have described an AMF as a small foramen in the area surrounding the MF (Riesenfeld, 1956;Sutton, 1974).…”
Section: Definition Of An Amfmentioning
confidence: 99%
“…In the clinical setting, the presence of an AMN can cause difficulties during oral surgery such as apical surgery (Concepcion and Rankow, 2000;Arx et al, 2014), implant surgery (Kulkarni et al, 2011;Pancer et al, 2014), local anesthesia (L opez and Diago, 2006), trauma surgery (Ramadhan et al, 2010;Mamatha et al, 2013), and neurectomy (Ca girankaya and Kansu, 2008;Jha and Kumar, 2012). Arx et al (2014) described four cases of apical surgery in which an AMN was present.…”
Section: Clinical Casesmentioning
confidence: 99%
“…The human MF presents typically as a single opening on each side of the mandible. However, in some cases, multiple foramina may be observed (4,(7)(8)(9). Rare cases of MF absence have been reported (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Concepcion et al (14) encountered an accessory branch of mental nerve adjacent to the MF during flap reflection in a periapical surgery. Çagi-rankaya et al (15) presented a case of AMF below the apex of the first molar demonstrated with intraoral radiographies for periodontal treatment.…”
mentioning
confidence: 98%